ANALISIS YURIDIS PERBUATAN MELAWAN HUKUM PELAKU USAHA PAKAIAN BEKAS DALAM PERDAGANGAN BARANG YANG DILARANG IMPOR - NIM. A1011211274, EGHA PUTRI NUR EFFENDY (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Clothing is an essential basic need for humans. Various types of clothing circulate among the Indonesian community, one of which is imported second-hand clothing. Imported second-hand clothing is clothing that has been used by previous users and then imported from one country to another. The Indonesian government has enacted regulations prohibiting the import of used clothing. Although the government has issued a ban outlined in the Regulation of the Minister of Trade of the Republic of Indonesia Number 40 of 2022 concerning prohibited imported goods, the sale of imported second-hand clothing is still rampant to this day. Of course, this activity is illegal and violates existing and applicable regulations, and the actions taken by these business operators fall under unlawful acts in accordance with Article 1365 of the Civil Code. Thus, the author formulates the research problem as follows